Effects of Banana Peel Liquid Organic Fertilizer and Chicken Manure on Growth and Yield Components of Soybean (Glycine max L.) in Andisol Soil - Fenty Maimunah Simbolon; Dwi Agung Heryando Saragih; R Rahmawati; Sri Hafnida Ritonga (CV. Media Digital Publikasi Indonesia, 2026)
This study evaluated the effects of banana peel liquid organic fertilizer (LOF) and chicken manure on the growth and yield components of soybean (Glycine max L.) cultivated in Andisol soil. The experiment was conducted from December 2020 to April 2021 at the experimental field of the Faculty of Agriculture, Universitas Islam Sumatera Utara, using a factorial randomized block design with two factors: four doses of banana peel liquid organic fertilizer (0, 50, 100, and 150 mL polybag⁻¹) and four rates of chicken manure (0, 5, 10, and 15 t ha⁻¹). Data were analyzed using analysis of variance followed by Duncan's Multiple Range Test at the 5% significance level. The results showed that banana peel liquid organic fertilizer significantly increased the number of branches and the weight of 100 seeds but had no significant effect on plant height, stem diameter, or the number of pods. Chicken manure significantly increased stem diameter, number of branches, number of pods, and weight of 100 seeds, whereas its effect on plant height was not significant. No significant interaction was observed between banana peel liquid organic fertilizer and chicken manure for any of the observed variables. These findings indicate that both organic fertilizers independently improved soybean growth and yield components in Andisol soil, although their combined application did not produce a synergistic effect. Further studies involving comprehensive soil characterization, nutrient uptake, and economic evaluation are recommended to better understand the agronomic potential of banana peel liquid organic fertilizer under different environmental conditions.